Mechanical Performance Analysis of Steel Beam-Column Joints in Fabricated Multirise Steel Structures after Fire - Fang Liu; Xiuli Wang; Bin Cai; Xuguang Li; Liqi Yang (Journal of Chemistry)
This study aims to analyze the mechanical properties of fabricated multistory and high-rise steel structures and steel beam-column joints after fire. Considering that the steel structure building has the characteristics of good seismic resistance, flexible structural layout, short construction period, and good safety, first, the thermal and mechanical properties of steel are analyzed. They are thermal conductivity, the thermal expansion coefficient of steel, yield strength, and elastic modulus of ordinary steel. Next, the thermal conduction principle of steel under fire environment is analyzed, including thermal conduction, thermal convection, and thermal radiation. Then, the three-story and three-span reinforced concrete is selected as the experimental object. The local frame calculation model is established through the finite element software Abaqus. It is found that when the axial compression ratio is 1.0 and the fire time of the steel body is 180 min, the vertical deformation speed of the middle column and side column of the frame will increase rapidly. Besides, the bending moment at the bottom of the side column of the frame will increase inversely. The change is not obvious when the axial compression ratio is other values. The axial deformation of the universal beam is obvious under the condition of different fire load ratios. When the load ratio increases, the maximum fire resistance of the universal beam will decrease rapidly. Meanwhile, when the steel body is subjected to the same load ratio, different bearing capacity β has little effect on the fire resistance limit of the steel body. This thesis focuses on a series of changes in the steel of fabricated multistory and high-rise steel buildings after the fire, hoping to provide a reference for the relevant teams of steel construction and make the future housing construction safer.